Vicenarian Professionals’ Awareness and Determinants of Engagement in Cryptocurrency in Koronadal City, South Cotabato, Philippines - Jayson Diaz; Mikko Abang; Maria Atam; Mark Ballados (Universitas Dinamika, 2023)
This research delves into investigating the awareness and engagement of vicenarian professionals with cryptocurrency and the digital economy in Koronadal City, Philippines. The study examined the demographic profiles to gain a comprehensive understanding of the participants. Furthermore, it assesses the participants' level of awareness concerning cryptocurrency applications, trading platforms, and associated risks and opportunities. To achieve its objectives, the research adopts a descriptive multivariate correlational approach, leveraging confirmatory predictive analysis to identify significant factors influencing engagement. The study reveals a balanced gender distribution among the participants, showcasing diverse income levels and educational backgrounds. Interestingly, most respondents demonstrate neutral levels of awareness concerning cryptocurrency applications and the associated risks and opportunities. Surprisingly, technological awareness, economic conditions, government regulations, and security concerns do not emerge as significant factors influencing engagement. However, the study uncovers that social media factors play a pivotal role as a significant determinant of engagement among vicenarian professionals. This finding provides valuable insights for policymakers and industry stakeholders aiming to boost cryptocurrency and digital economy participation among young professionals in the region.